2015
DOI: 10.5539/ies.v8n11p50
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of IPad on School Preparedness among Preschool Children with Hearing-Impairments

Abstract: With modern technological developments and with the fast expansion of mobile technical equipment, conducting a field study to find out how technology influences various developmental aspects of normal and special needs children at the preschool stage was deemed appropriate and timely hearing impairment. In this study aimed at finding out the effect of iPad on school preparedness among school children with hearing impairment. In this study, the children attended the national kindergarten in Al-Riyadh. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In addition to its ability to improve physical fitness, motor skills, and is highly motivating for physical exercise, studies have also shown that exergamesare capably alleviating characteristic loneliness in challenged children through increased group participation via multiple players mode [16]. Exergames have also been reported amongst other technology-oriented interventional studies related to children with hearing impairment [17], [18]. However, the only related study to FMS development in hearing-impaired children is in [19], where the balance ability of adolescents with hearing impairments were tested after an exergame-based balance training.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition to its ability to improve physical fitness, motor skills, and is highly motivating for physical exercise, studies have also shown that exergamesare capably alleviating characteristic loneliness in challenged children through increased group participation via multiple players mode [16]. Exergames have also been reported amongst other technology-oriented interventional studies related to children with hearing impairment [17], [18]. However, the only related study to FMS development in hearing-impaired children is in [19], where the balance ability of adolescents with hearing impairments were tested after an exergame-based balance training.…”
Section: Introductionmentioning
confidence: 98%
“…The use of electronic and digital technologies in the education of children has risen significantly in recent years, particularly children with hearing and hearing loss [17]. Some countries are making concerted efforts to introduce children with special needs into the digital world, particularly those with hearing impairment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its ability to improve physical fitness, motor skills, and is highly motivating for physical exercise, studies have also shown that exergames are capably alleviating characteristic loneliness in challenged children through increased group participation via multiple players mode (Vaghetti et al, 2018). Exergames have also been reported amongst other technology-oriented interventional studies related to children with hearing impairment (Turkestani, 2015;Havenga et al, 2017). However, the only related study to FMS development in hearing-impaired children is in (Vernadakis et al, 2018), where the balance ability of adolescents with hearing impairments were tested after an exergame-based balance training.…”
Section: Introductionmentioning
confidence: 99%
“…The use of electronic and digital technologies in the education of children has risen significantly in recent years, particularly children with hearing and hearing loss (Turkestani, 2015). Some countries are making concerted efforts to introduce children with special needs into the digital world, particularly those with hearing impairment.…”
Section: Introductionmentioning
confidence: 99%